Realist paradigm of international relations power, systems and game theories - Mukhopadhyay, Amartya (Routledge, Taylor & Francis Group, 2024)
"This book explores realist theories-also called power politics approaches, formulations of systems theories, and game theory in International Relations (IR). The first section of the book focuses on theories of Early Classical Realism-Thucydides, Machiavelli, and Hobbes, and two Asian exponents-Kautilya and Han Fei Tzu. It covers the rise and fall of different schools of imperial geopolitics including those developed during the Cold-War and postmodern periods. It also discusses theories proposed by three stalwarts of Neoclassical Realism- Niebuhr, Carr, and Morgenthau; the Neorealism of Waltz; Strategic Realism of Schelling; and Offensive Realism of Mearsheimer. The book also examines theoretic formulations of Kaplan, Modelski, Rosecrance, McClelland, Holsti, and Singer, as well as game theory and its relevance and application in international relations. It explores diverse variants of theories of power in international relations through a critical readings of texts and IR literature. This book will be of interest to researchers and students of political science, international relations, history and law."
2309
Keywords: Internationale Politik; Politischer Realismus; Political realism; Balance of power; International relations / Philosophy